Damonstrative behavior and its motivation - Viliūnas, Vytis; Kravčenko, Anna (Psichologija, 2000)
The article on the basis of zoopsychological and psychopathological data investigates the meaning of demonstrative motivation for human behavior. Animal studies show that a single clear determined demonstration phenomenon does not exist. Demonstration in a wide sense is the component part of communication, so it can be initiated by any motivation, providing for contacts between individuals. Demonstration in the narrow sense, discussed in the article, is most distinctly expressed in behavior, aroused by propagative, hierarchy relations, territorial and defensive motivation. The existence of functionally autonomic need for self-demonstration, independent from other kinds of motivation, is discussed in the context of the such problems as instinct organization and phylogenetic development of motivation. This need is a result of the gradual separation (emancipation) in evolution of demonstrative elements from the needs, to which they were initially subordinated. Psychopathological data shows that demonstration most intensively and frequently reveals itself in hysterical type deviations. Human demonstration is amazingly diverse, with inherent secret expression of conversion self-demonstration, when somatic illnesses are imitated in order to have everyone’s attentions. Hysterical symptoms most convincingly substantiates the existence of functionally autonomic motivation of demonstration, the rudiments of which are observed in animal behavior. Among various deviations of this motivation, light hysteria forms, the pathology of which is usually doubtful, should be singled out, as well as the cases of hysteroidic psychopathy and accentuation, the description of which refers to an insatiable passion for turning attention at oneself as to the main particularity. It is reasoned that psychopathic traits should be treated not as cases of pathology but as extreme variations of a norm. Such interpretation, first of all, significantly advocates the statement that the need for demonstration is characteristic of a human being and is a crucial part of his/her basic motivation. The second important conclusion drawn from such comprehension of psychopathies is that, due to genetic variability, human beings originally differ in expression of the need in question (as well as other needs). Motives stimulating phylogenetically primary instrumental employment of self-demonstration are not, in the case of a human being, strictly regulated; thus they become considerably diverse. Among different cases of instrumental self-demonstration, its defensive employment should be singled out, which is aimed at avoidance of traumatizing events or at mitigation of their after-effects.